2016
DOI: 10.1007/s00572-016-0748-6
|View full text |Cite
|
Sign up to set email alerts
|

Scleroderma areolatum ectomycorrhiza on Fagus sylvatica L.

Abstract: Despite its broad host range and distribution and its potential applications in commercial plantation forests, comprehensive descriptions of Scleroderma ectomycorrhizae are available only for Scleroderma citrinum, Scleroderma bovista and Scleroderma sinnamariense. This study provides a morphological and anatomical description of tree nursery derived ectomycorrhizae of Scleroderma areolatum on Fagus sylvatica, grown for several years in a climatized room. Ectomycorrhizae of S. areolatum were silvery white with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
0
15
0
3
Order By: Relevance
“…Based on these results and on the outcomes of recent phylogenetic studies on Scleroderma (Phosri et al 2009;Rusevska et al 2014;Mrak et al 2016), sequences were retrieved from GenBank (https://www.ncbi.nlm.nih.gov/nucleotide/) and UNITE (http://unite.ut.ee/) databases for a comparative phylogenetic analysis. After excluding the ambiguous regions at the 5′ and 3′ ends of the chromatograms, sequences were edited using BioEdit v. 7.2.5 (Hall 1999) and aligned with MAFFT programme (https://mafft.cbrc.jp/alignment/ software/) using the E-INS-i aligning strategy (Katoh et al 2005).…”
Section: Molecular Analyses and Phylogenetic Inferencementioning
confidence: 99%
See 2 more Smart Citations
“…Based on these results and on the outcomes of recent phylogenetic studies on Scleroderma (Phosri et al 2009;Rusevska et al 2014;Mrak et al 2016), sequences were retrieved from GenBank (https://www.ncbi.nlm.nih.gov/nucleotide/) and UNITE (http://unite.ut.ee/) databases for a comparative phylogenetic analysis. After excluding the ambiguous regions at the 5′ and 3′ ends of the chromatograms, sequences were edited using BioEdit v. 7.2.5 (Hall 1999) and aligned with MAFFT programme (https://mafft.cbrc.jp/alignment/ software/) using the E-INS-i aligning strategy (Katoh et al 2005).…”
Section: Molecular Analyses and Phylogenetic Inferencementioning
confidence: 99%
“…About 25 species are currently recognized (Kirk et al 2008), although much work on the delimitation of taxa and their phylogenetic relationships is still ongoing (Phosri et al 2009;Wilson et al 2012;Rusevska et al 2014), and so is the identification of new species (Baseia et al 2016;Crous et al 2016). Species of Scleroderma establish ectomycorrhizal (ECM) symbiosis with a range of coniferous and non-coniferous trees and shrubs, both in temperate and tropical regions, with little tendency to host specificity (Jeffries 1999;Mrak et al 2016). It has been suggested that the ectomycorrhizal generalist habit has facilitated the wide distribution of Scleroderma and other Sclerodermatineae groups (Wilson et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes morphoanatomical-based taxonomy is not well supported by molecular taxonomy. To overcome such discrepancy, the combined approach of morphoanatomical and molecular characterization of ectomycorrhizas in combination with phylogeny was applied [12].…”
Section: Introductionmentioning
confidence: 99%
“…Es de distribución gregaria o cespitosa, epigeo en el suelo o humus con musgos, a veces en la madera podrida (6). En el mundo se ha asociado a los géneros Castanea, Quercus, Fagus, Nothofagus y Pinus (7). Su uso culinario es discutido, siendo consumido en algunos países de Europa del este.…”
Section: Introductionunclassified